Effect of Bonding System on Composite Discoloration - عبدالله, عاطف (Latakia University Journal -Medical Sciences Series, 2020)
Objective: The purpose of this study is to investigate the effect of bonding type of Composite Discoloration to investigate the best kind of bonding in clinical performance. Materials and Methods: Tetric N Ceram composite of Ivoclar Vivadent Company was used. Forty conventional class V fillings were prepared in dimensions (2x2x2) mm on the buccal surface of first and second premolars of (20) patients in which (20) restorations were performed with dry bond in group number 1 and (20) restorations were performed with wet bond in group number 2 then All restorations were observed for (one month, 6 months) to investigate discoloration. Results: Wet bonding group revealed significant less discoloration than dry bonding group.